2019
DOI: 10.3238/arztebl.2019.0445
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Rapid Tranquilization in Aggressive Behavior

Abstract: ggressive behavior can be considered pathological only when it arises in the context of disease. It is thus not necessarily an indication for medical treatment. Not only emergency medical personnel and psychiatrists, but also family physicians are often confronted with the question of how to treat aggressive behavior. In one study, psychiatric emergencies accounted for 11.8% of all emergency medical interventions outside the hospital. Psychomotor agitation made up 28% of all psychiatric emergencies, second onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…disorders. Instead, they might have been used to address insomnia [62,63], control agitation and aggressive behaviour [64] or to treat comorbid psychotic symptoms. Augmentation therapy was identified to be superior to monotherapy with either antidepressant or antipsychotic drugs and to placebo in the acute treatment of psychotic depression [65,66], which accounted for 7.4% of our total sample (see Table 1).…”
Section: Plos Onementioning
confidence: 99%
“…disorders. Instead, they might have been used to address insomnia [62,63], control agitation and aggressive behaviour [64] or to treat comorbid psychotic symptoms. Augmentation therapy was identified to be superior to monotherapy with either antidepressant or antipsychotic drugs and to placebo in the acute treatment of psychotic depression [65,66], which accounted for 7.4% of our total sample (see Table 1).…”
Section: Plos Onementioning
confidence: 99%
“…However, not all antipsychotics were necessarily administered to address depressive disorders. Instead, they might have been used to address insomnia [59,60], control agitation and aggressive behaviour [61] or to treat comorbid psychotic symptoms. Augmentation therapy was identified to be superior to monotherapy with either antidepressant or antipsychotic drugs and to placebo in the acute treatment of psychotic depression [62,63], which accounted for 7.4% of our total sample (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent Cochrane review concluded that the evidence for the use of benzodiazepines is not high, and that the advantage of adding a benzodiazepine to other drugs is not entirely clear, also in light of potential additive adverse effects ( 11 ). Others have concluded that a first-generation antipsychotic together with lorazepam or monotherapy with lorazepam or a second-generation antipsychotic are effective therapeutic options for acute agitation ( 4 , 12 ).…”
Section: Introductionmentioning
confidence: 99%